Multi-Agent Collaborative Robots With Adaptive Sensor Fusion for Monitoring and Mitigation of Emergency Situations - Yevsieiev, V.; Demska, N. (ХНУРЕ, 2026)
The paper considers an approach to using multi-agent collaborative robotic systems with adaptive sensor fusion for monitoring and mitigation of emergency situations. A system architecture is proposed in which a group of mobile robots cooperatively collects, integrates, and analyzes sensor data to form a consistent representation of the environment and support decision making. It is shown that the use of adaptive sensor information integration increases the system’s robustness to noise and failures of individual agents. The presented results of numerical simulations confirm the effectiveness of the proposed approach under dynamic and uncertain conditions..
Keywords: multi-agent systems; collaborative robots; emergency response.; adaptive systems